Putting different price tags on the same health condition: Re-evaluating the well-being valuation approach - Nattavudh Powdthavee; Bernard van den Berg (Institute for the Study of Labor (IZA), 2011)
Many recent writings in health policy have proposed that health be valued directly and in monetary terms using the new well-being valuation method. Yet there is currently no clear consensus on what the best measure of individual's experience may be for the evaluation process. To shed light on this issue, monetary values for a number of health problems are compared across different well-being measures within the same UK data set. We find that, while there is strong internal consistency of health impacts within each well-being measure, hugely different monetary valuations are obtained for the same health problem across different well-being measures. Our results, although should only viewed as illustrative, call for economists to rethink about which measure of well-being or experienced utility to be used in the well-being valuation method, should the approach ever be implemented in real policy contexts.
urn:nbn:de:101:1-201104113663
Keywords: H8; I18; I31; 330; well-being; compensation variations; monetary valuations; happiness; health; GHQ; Gesundheit; Bewertung; Lebensqualität; Zufriedenheit; Großbritannien